Genome-wide association studies reveals new candidate genes associated with resistance to Striga gesneroides in Cowpea [Vigna unguiculata (L.) Walp.] accessions from sub-Saharan Africa - (:unkn) unknown (My University, 2024)
Source Agritrop Cirad (https://agritrop.cirad.fr/609970/) * Autres projets (id;sigle;titre): NER-17-0005;;(NOR) Climate-Smart Agricultural Technologies for improved Rural Livelihoods and Food Security//
Keywords: African Research